Efektivitas Metode Al-Jurumiyah dalam Meningkatkan Pemahaman Kitab Kuning di Pondok Pesantren Salafiyah Ibrahimy - Azaim, Moh; Husni, Muhammad (Institut Agama Islam Sultan Muhammad Syafiuddin Sambas, 2025)
Understanding the Arabic text is a fundamental skill for students in Salafiyah Islamic boarding schools. However, many novice students struggle to read Arabic texts due to their weak mastery of basic grammar. This Community Service Program (PKM) aims to implement and measure the effectiveness of the Al-Jurumiyah method in improving students' understanding of Arabic sentence structure at the Ibrahimy Salafiyah Islamic Boarding School. The implementation method included structured training, intensive mentoring, reading exercises, and evaluation through pre- and post-tests. The results showed a significant increase in understanding of basic grammar rules and reading ability in the Arabic text. These findings confirm that the Al-Jurumiyah method is highly relevant as an approach to teaching basic grammar for novice students. This program is expected to continue as a model for teaching Arabic grammar in Islamic boarding schools.